Bilayer Molecular Assembly at a Solid/Liquid Interface as Triggered by a Mild Electric Field1. (6th November 2014) - Zheng, Qing‐Na; Liu, Xuan‐He; Liu, Xing‐Rui; Chen, Ting; Yan, Hui‐Juan; Zhong, Yu‐Wu; Wang, Dong; Wan, Li‐Jun
Abstract The construction of a spatially defined assembly of molecular building blocks, especially in the vertical direction, presents a great challenge for surface molecular engineering. Herein, we demonstrate that an electric field applied between an STM tip and a substrate triggered the formation of a bilayer structure at the solid–liquid interface. In contrast to the typical high electric‐field strength (109 V m−1) used to induce structural transitions in supramolecular assemblies, a mild electric field (105 V m−1) triggered the formation of a bilayer structure of a polar molecule on top of a nanoporous network of trimesic acid on graphite. The bilayer structure was transformed into a monolayer kagome structure by changing the polarity of the electric field. This tailored formation and large‐scale phase transformation of a molecular assembly in the perpendicular dimension by a mild electric field opens perspectives for the manipulation of surface molecular nanoarchitectures.